Urinary Aldosterone Analysed by LC-MS/MS vs Immunoassay for Diagnosis of Primary Aldosteronism - Moe Thuzar; Alexandra Matthews; David Je; Jinwen He; Sheree Stoner; Greg Ward; Elisabeth Ng; Jun Yang; Diane Cowley; Bo Li; Brett C McWhinney; Jacobus P Ungerer; et al. (The Journal of Clinical Endocrinology & Metabolism, 2026)
Abstract Context The performance of 24-hour urinary aldosterone (24hr-UAldo) analysed by liquid chromatography-mass spectrometry (LC-MS/MS) (24hr-UAldo-LCMS) for diagnosis of primary aldosteronism (PA) is not established. Objective To assess the diagnostic performance of 24hr-UAldo-LCMS, vs that measured by immunoassay (24hr-UAldo-IA), for diagnosing PA. Design, Setting and Patients A cohort study involving 182 prospectively-collected 24hr-urine samples from 167 patients who had hypertension with elevated plasma aldosterone-renin ratio and/or adrenalectomy for unilateral PA, 24-hour urinary sodium (24hr-UNa) measured and seated saline suppression test (SSST) performed, off interfering medications and on unrestricted dietary sodium, over a 5-year period at a tertiary centre. Interventions and Main Outcome Measures 24hr-UAldo-LCMS was analysed in 182 samples and 24hr-UAldo-IA concurrently in a subset of 121 stored samples. Receiver operating characteristic curve analyses were performed to assess performance of 24hr-UAldo at various 24hr-UNa for diagnosing PA using SSST as the reference test. Results Mean ± SD 24hr-UAldo-LCMS was higher in cases with positive SSST (n = 127) vs those with negative SSST (n = 55) (50.6 ± 35.7 vs 20.8 ± 13.9 nmol/24 h; P < 0.05). 24hr-UAldo-LCMS ≥23.5 nmol/24 h had 92.1% sensitivity and 82.6% specificity (area under the curve [AUC] = 0.946), while a higher cut-off of ≥27.5 nmol/24 h provided a higher specificity (92.3%) with 78.9% sensitivity to identify PA in those with 24hr-UNa ≥190 mmol/24 h, the 24hr-UNa level with optimal 24hr-UAldo performance. The specificity of 24hr-UAldo-IA was inferior: 66.7% (92.3% sensitivity) at 24hr-UAldo-IA ≥24.5 nmol/24 h (AUC=0.81) and 77.8% (73% sensitivity) at 24hr-UAldo-IA ≥35.5 nmol/24 h, when 24hr-UNa ≥190 mmol/24 h. Conclusion 24hr-UAldo-LCMS in the setting of 24hr-UNa ≥190 mmol/24 h can diagnose PA with high sensitivity and specificity, at lower cut-offs than 24hr-UAldo-IA